1998
DOI: 10.1007/s001250051057
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and vanadate restore decreased plasma endothelin concentrations and exaggerated vascular responses to normal in the streptozotocin diabetic rat

Abstract: Type I (insulin-dependent) diabetes mellitus is associated with metabolic and cardiovascular abnormalities as exemplified by the streptozotocin (STZ) induced diabetic rat. Along with profound hyperglycaemia and reduced plasma insulin concentrations, STZ rats shaw altered responses to vasoconstrictor stimuli, and over time, develop complications characteristic of Type I diabetes [1]. Endothelin has been implicated in various disorders such as renal disease, atherosclerosis, diabetes mellitus and hypertension [2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 41 publications
1
8
0
2
Order By: Relevance
“…With the present study we demonstrate that STZ-induced diabetes is a model of insulin-dependent diabetes (type 1) and that STZ-dependent vascular complications are probably not associated with systemic toxic side effects but strictly depend on insulin deficiency. These findings are in good agreement with previous reports on insulin replacement therapy, in which insulin completely normalized the adverse effects of STZ on vascular responsiveness and vascular superoxide formation [28], on blood glucose levels and weight gain [27] as well as on STZ-triggered vasoconstrictive responses to both endothelin-1 and methoxamine [50]. More support for our concept came from Higashi et al [29], who reported that retinal blood flow is decreased in diabetic rats and normalized by insulin therapy, although these authors used a different protocol for induction of diabetes and found that vascular abnormalities are not completely reversed by short-term insulin therapy upon long-term untreated diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…With the present study we demonstrate that STZ-induced diabetes is a model of insulin-dependent diabetes (type 1) and that STZ-dependent vascular complications are probably not associated with systemic toxic side effects but strictly depend on insulin deficiency. These findings are in good agreement with previous reports on insulin replacement therapy, in which insulin completely normalized the adverse effects of STZ on vascular responsiveness and vascular superoxide formation [28], on blood glucose levels and weight gain [27] as well as on STZ-triggered vasoconstrictive responses to both endothelin-1 and methoxamine [50]. More support for our concept came from Higashi et al [29], who reported that retinal blood flow is decreased in diabetic rats and normalized by insulin therapy, although these authors used a different protocol for induction of diabetes and found that vascular abnormalities are not completely reversed by short-term insulin therapy upon long-term untreated diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…In the STZ model, injection of STZ destroys the insulin secreting b-cells of the pancreas and these rats develop severe chronic hyperglycemia analogous to type 1 (insulin-dependent) diabetes mellitus [24]. In contrast with other models, blood pressure in these rats is reduced beginning at 2 weeks after injection [25].…”
Section: Discussionmentioning
confidence: 98%
“…Vascular elaboration of endothelin promotes glomerular damage by augmenting vasoconstriction, glomerular permeability, mesangial cell proliferation, and extracellular matrix production (22). In support of this view, it has been reported that plasma endothelin antigen and vascular cell endothelin mRNA are increased in both humans with diabetes and in STZ-treated rats (27). Moreover, increased plasma endothelin levels in diabetes are associated with an elevated risk of microvascular complications, suggesting a possible link between endothelin and microangiopathy (1,18).…”
Section: Role Of Endothelin Signaling In Diabetesmentioning
confidence: 90%